Reifying difference: Examining the negotiation of internal diversity on a (post-)lesbian subreddit. (October 2019) - Foeken, Elsie; Roberts, Steven
This article contributes to the study of contemporary lesbian communities by examining the management of internal diversity on a lesbian 'subreddit' (i.e. a sub-section of the popular social news media website Reddit ) in relation to the parallel conceptual categories of 'post-gay' and 'post-lesbian'. Drawing on data obtained via virtual ethnography of this subreddit, it argues that contemporary lesbian communities have diverged significantly from their history of suppressing internal diversity in order to produce a stable category of collective identification. Rather, members of this community drew upon ideals typical of the post-gay era by celebrating internal differences made real through a 'minoritising' logic of multi-'ethnicity'. The article closes with implications for future research into (post-)lesbian communities.